METHODS AND TECHNIQUES OF CRITICAL THINKING TECHNOLOGY IN MATHEMATICS LESSONS (American Journal of Interdisciplinary Research and Development, 2022)
Mathematics as a science aims to develop general rules to be applied in specific situations. The article discusses ways to develop logical thinking in mathematics lessons.